Pengaruh Tingkat Inflasi dan Suku Bunga BI Rate Terhadap Indeks Sektor Konsumsi - Kristiana Oktavia; Robiyanto Robiyanto (Jurnal Pasar Modal dan Bisnis, 2021)
This research is intended to analyze the effect of inflation and BI rate on the consumption sector index. This type of research data is quantitative method which is secondary data in the form of a monthly basis from 2015 to 2020 using the GARCH technique. The results showed that inflation and BI rate positive insignificant effect on the consumption sector index from 2015 to 2020. The result of this study implicated that investors can consider external factors in making investments. The results of the study have limitations only using 2 macro variables which are very commonly used, it is better if for further research to use more maro variables and add micro variables. Then can use other sector indexes in research and can conduct new research by comparing the period before the pandemic and during the Covid-19 pandemic.